The natural anti-gal antibody as foe turned friend in medicine - Galili, Uri (Academic Press, an imprint of Elsevier, 2018)
The Natural Anti-Gal Antibody as Foe Turned Friend in Medicine provides a comprehensive review of the natural anti-Gal antibody, which is the most abundant antibody in humans constituting ~1% of immunoglobulins and the carbohydrate antigen it recognizes, the?-gal epitope. It discusses the discovery of this antigen/antibody system, its evolution in mammals, the pathological effects of this antibody, and its possible use in various therapies in humans. Most significantly, the book discusses microbial and regenerative therapies in which an antibody present in all humans may be harnessed as an in vivo pharmaceutical agent that enables a wide variety of therapies. Some of these therapies are described as experimental studies that are compiled in this book, other already studied therapies in the area of cancer immunotherapy are also included in this book.